Effectiveness of Concept Mapping and Branching Programming Learning Material on Achievement in Economics - Joshi, Neeraj; Tuteja, Anmol; Millwala, Sakina (Indian Journal of Educational Technology, 2025)
The title of the research was “Effectiveness of Concept Mapping and Branching Programming Learning Material on Achievement in Economics”. The objectives of the study were (i) To compare the mean ranks of gain scores of the Traditional lecture group and Concept Mapping group and (ii) To compare the mean ranks of gain scores of the Traditional lecture group and the Branching Programming Learning Material group. (iii) To compare the mean rank of gain scores for the Concept Mapping group and Branching Programming Learning Material group. A purposive sampling technique was used by the researcher in which the sample size was 67, from which 25 students were from experimental group 1 (Concept Mapping group), 25 students were from experimental group 2 (Branching Programming Learning Material group), and 17 students were from the Traditional lecture group, for data collection self-made Achievement test was used. The non-equivalent control group design was used for this study, and data was collected from two schools in Indore. The treatment was given to experimental groups for 9 days, including administration of pre and post-tests. The Mann-Whitney U test was used to analyze the objectives. The findings of the research were that (i) The mean ranks of the Concept Mapping group were significantly higher than those of the traditional lecture group, (ii) The mean ranks of the Branching Programming Learning Material group were significantly higher than those of the traditional lecture group, (iii) The mean ranks of Branching Programming Learning Material group was significantly higher than Concept Mapping group.